Stress‐Regulation Design of Mesoporous Carbon Spheres Anodes with Radial Pore Channels Toward Ultrastable Potassium‐Ion Batteries - Shuming Dou; Qiang Tian; Tao Liu; Jie Xu; Lingyan Jing; Cuihua Zeng; Qunhui Yuan; Yunhua Xu; Zheng Jia; Qiong Cai; Wei-Di Liu; S. Ravi P. Silva; et al. (Small Science, 2022)
Electrochemical energy storage (EES) devices are expected to play a critical role in achieving the global target of “carbon neutrality” within the next two decades. Potassium‐ion batteries (KIBs), with the advantages of low cost and high operating voltage, and they could become a major component of the required energy‐material ecosystems. Carbon‐based materials have shown promising properties as anode materials for KIBs. However, the key limitation of carbon anodes lies in the dramatic mechanical stress originating from large volume fluctuation during the (de)potassiation processes, which further results in electrode pulverization and rapid fading of cycling performance. Here, a controllable self‐assembly strategy to synthesize uniform dual‐heteroatom doped mesoporous carbon sphere (DMCS) anodes with unique radial pore channels is reported. This approach features a modified Stöber method combined with the single‐micelle template from the molecule‐level precursor design. The DMCS anodes demonstrate exceptional rate capability and ultrahigh cycling stability with no obvious degradation over 12 000 cycles at 2 A g−1, which is one of the most stable anodes. Furthermore, finite element simulations quantitatively verify the stress‐buffering effect of the DMCS anodes. This work provides a strategy from the perspective of stress evolution regulation for buffering mechanical stress originating from large volume fluctuations in advanced KIBs electrodes.